Sacral nerve modulation for faecal incontinence: influence of age on outcomes and complications. A multicentre study. (18th May 2019) - Mege, D.; Meurette, G.; Brochard, C.; Damon, H.; Lambrescak, E.; Faucheron, J.‐L.; Wyart, V.; Lehur, P.‐A.; Sielezneff, I.; Siproudhis, L.; Mion, F.; Etienney, I.; et al.
Abstract: Aim: Faecal incontinence is frequent in the elderly. Little is currently known about the efficacy of sacral nerve modulation (SNM) in the elderly. The present study aimed to assess the impact of age on the outcome of SNM and on the surgical revision and explantation rates by comparing the results of a large data set of patients. Method: Prospectively collected data from patients who underwent an implant procedure between January 2010 and December 2015 in seven French centres were retrospectively evaluated. In total, 352 patients [321 women; median age (range): 63 (24–86) years] were included. Clinically favourable and unfavourable outcomes, and surgical revision and explantation rates, were compared according to the age of the patients. Results: A similar outcome was observed when comparing patients < 70 years and ≥ 70 years (a favourable outcome in 79.2% and 76.2%, respectively, P  =   0.89). The probability of a successful treatment as a function of time was similar for the two age groups (< 70 years and ≥ 70 years, P  =   0.54). The explantation and revision rates were not influenced by age (explantation rate: 17% in patients < 70 years vs 14% in patients ≥ 70 years, P  =   0.89; and revision rate: 42% in patients < 70 years vs 40% in patients ≥ 70 years, P  =   0.89). The probability of explantation as a function of time was similar for the two age groups ( P  =   0.82). The limitations of this study were its retrospective status, the rate of loss at follow‐up and different durations of patient follow‐up. Conclusions: Our results suggest that patients ≥ 70 years suffering from faecal incontinence benefit from SNM with a similar risk as a younger population.